2017
DOI: 10.1371/journal.pone.0185165
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in feeding strategies of Galapagos sea lions: A case of trophic specialization

Abstract: The trophic behavior of marine predators varies according to the level of competition to which they are exposed. In general, populations that inhabit lower productivity systems face a strong intraspecific competition, which contributes to the development of different foraging strategies to maximize nutritional efficiency. Given the high trophic flexibility of Zalophus wollebaeki, this species is considered appropriate for the analysis of such behavior. Furthermore, this trophic flexibility has allowed them to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 61 publications
7
36
0
Order By: Relevance
“…For adult female pinnipeds, body condition is often indicative of acute differences in foraging and lactation efficiency within the current environmental landscape (Crocker and McDonald 2016 ). Specific to Galapagos sea lions, adult females show unusually high diversity in intraspecific foraging strategies with associated metabolic costs and dietary specializations (Villegas-Amtmann et al 2008 , 2017 ; Paez-Rosas et al 2017 ), all of which may underscore body condition differences found here. In controlled studies, offspring often have marked increases in testosterone and masculinization of traits when the maternal diet is optimal during gestation, potentially because of the high metabolic demands required to facilitate androgens in utero (Rosenfeld and Roberts 2004 ; Pike and Petrie 2005 ).…”
Section: Discussionmentioning
confidence: 56%
“…For adult female pinnipeds, body condition is often indicative of acute differences in foraging and lactation efficiency within the current environmental landscape (Crocker and McDonald 2016 ). Specific to Galapagos sea lions, adult females show unusually high diversity in intraspecific foraging strategies with associated metabolic costs and dietary specializations (Villegas-Amtmann et al 2008 , 2017 ; Paez-Rosas et al 2017 ), all of which may underscore body condition differences found here. In controlled studies, offspring often have marked increases in testosterone and masculinization of traits when the maternal diet is optimal during gestation, potentially because of the high metabolic demands required to facilitate androgens in utero (Rosenfeld and Roberts 2004 ; Pike and Petrie 2005 ).…”
Section: Discussionmentioning
confidence: 56%
“…These differences are so pronounced that there is little overlap between animals of different groups, either because of a clear spatial separation of foraging habitats (benthic versus others), or because of a temporal and vertical separation (pelagic versus night). This separation might reduce intraspecific competition, as described in Antarctic fur seals (Kernaléguen et al 2015 ) and discussed for Galápagos sea lions (Páez-Rosas et al 2017 ), representing a strong driver for the development and stabilization of those foraging strategies. Avoidance of competition, however, might not be the only driver for the observed individual differences.…”
Section: Discussionmentioning
confidence: 89%
“…Trophic plasticity, on the other hand, is a form of trophic generalism, implying that a species is capable of feeding on a broad food spectrum, but will exploit only a (partly different) part of that spectrum depending on the competitive environment in which it occurs (here, e.g., in the different depth zones) (Hazlett, 1988;Bearhop et al, 2004;Gutt, 2006;Riera, 2009). The scenario of the existence of mainly trophic generalists on offshore wind turbines is plausible, because the species would be able to co-occur in a limited amount of space by exhibiting considerable trophic plasticity (Araújo et al, 2011;Páez-Rosas et al, 2017). In any case, the co-occurrence of multiple invertebrate species on offshore wind turbines could be partly explained by their feeding behavior.…”
Section: Introductionmentioning
confidence: 99%